Effect of contact stress on the cycle-dependent wear behavior of ceramic restoration. (April 2017) - Guo, Jiawen; Li, Ding; Wang, Haijing; Yang, Yanwei; Wang, Liying; Guan, Delin; Qiu, Yinong; He, Lin; Zhang, Shaofeng
Abstract: Aim: Ceramic restoration experiences the non-linear wear process during the chewing simulation, which contains running-in, steady and severe wear stages. However since various levels of contact stress may be applied on the occlusal surface during chewing, the cycle-dependent wear behaviors of ceramic crowns may differ. The aim of this study was to investigate the effect of contact stress on the development of wear behavior, as tested in a chewing simulator. Materials and methods: Thirty-six anatomical metal-ceramic crowns using Ceramco III as the veneering porcelain were randomly assigned to two groups based on the contact stress applied in the wear testing. Stainless steel balls served as antagonists. The specimens were dynamically loaded in a chewing simulator up to 2.4×10 6 loading cycles, with additional thermal cycling between 5 and 55℃. For each group, several checkpoints were employed to measure the substance loss of the crowns' occlusal surfaces and to evaluate the microstructure of the worn areas. Results: After 2.4×10 6 cycles, the ceramic restorations with lower contact stress demonstrated a long steady wear stage following the running-in, but without the severe wear stage. And a slowly microstructural degradation was observed that the subsurface defect could not be seen until final. With higher contact stress, however, the ceramic restorations experienced a faster transition from running-in to severe wear stage that the steady wear stage nearly disappeared. And an early formation of subsurface defects and the deterioration of microstructure were observed. Conclusions: Contact stress is a key factor affecting the wear development of ceramic restoration. The higher contact stress promotes the veneering porcelain to evolve into severe wear stage. In contrast, lower contact stress is prone to keep the veneering porcelain operating in steady wear stage, which delays the arrival of severe wear region. Graphical abstract: Highlights: The wear processes of porcelain in PFM crowns with different stresses were studied. Contact stress is a key factor affecting the cycle-dependent wear behavior. Higher contact stress promotes the porcelain to evolve into severe wear stage. Lower contact stress is prone to keep the porcelain operating in steady wear stage.